2016
DOI: 10.1371/journal.pone.0156162
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Growth of an Orthotopic Tumour Xenograft Model: Multi-Modal Imaging Assessment with Benchtop MRI (1T), High-Field MRI (9.4T), Ultrasound and Bioluminescence

Abstract: BackgroundResearch using orthotopic and transgenic models of cancer requires imaging methods to non-invasively quantify tumour burden. As the choice of appropriate imaging modality is wide-ranging, this study aimed to compare low-field (1T) magnetic resonance imaging (MRI), a novel and relatively low-cost system, against established preclinical techniques: bioluminescence imaging (BLI), ultrasound imaging (US), and high-field (9.4T) MRI.MethodsA model of colorectal metastasis to the liver was established in ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…BLI was used to confirm and monitor tumor growth over time because it is established as a reliable method for the assessment of brain tumor in non-clinical research due to its convenience in use and sensitiveness [3435]. In relation to these advantages, it was possible to monitor the growth of viable tumor cells from the inoculation with U87MG cells.…”
Section: Discussionmentioning
confidence: 99%
“…BLI was used to confirm and monitor tumor growth over time because it is established as a reliable method for the assessment of brain tumor in non-clinical research due to its convenience in use and sensitiveness [3435]. In relation to these advantages, it was possible to monitor the growth of viable tumor cells from the inoculation with U87MG cells.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Ramaswamy et al . demonstrated that low‐field magnetic resonance imaging (MRI) and US imaging have similar accuracies in determining tumor volume and growth . Given the low‐cost and high‐throughput platforms that exist for 3D structural mapping, US imaging is primarily preferred for measuring most solid tumors aside from those of the brain or bone.…”
Section: Role Of Us Imaging In Pdtmentioning
confidence: 99%
“…In preclinical xenograft models, Ayers et al have demonstrated that the volume of tumors measured via US is more accurate and requires~30% fewer animals to reach statistical significance when compared to standard caliper measurements (42). In another study, Ramaswamy et al demonstrated that low-field magnetic resonance imaging (MRI) and US imaging have similar accuracies in determining tumor volume and growth (43). Given the low-cost and high-throughput platforms that exist for 3D structural mapping, US imaging is primarily preferred for measuring most solid tumors aside from those of the brain or bone.…”
Section: Monitoring Tumor Structural and Morphological Changes Due Tomentioning
confidence: 99%
“…The goal is to advance state-of-the-art animal imaging technology at the anatomical and functional level (https://mris.uchicago.edu/). Many experimental studies of NHPs that focus on research questions including brain development, brain structural changes, and functional studies of different brain regions have been conducted using other types of 9.4 T MRI scanners such as the 9.4 T/35 cm scanner in Germany (Goebel et al 2009) and France (Même et al 2015) and the 9.4 T/39 cm scanner at University College London Centre for Advanced Biomedical Imaging, London (Ramasawmy et al 2016).…”
Section: State Of the Art At High Field Mrimentioning
confidence: 99%